Analysis of Greenhouse Gases Emissions and Feasibility of Mitigations Options for Dairy Farms in China - Wang, Wei; Lou, Chenglong; Zijlstra, Jelle; Sun, Xiaoge; Hao, Yangyi; Li, Shengli (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Climate change has gained increased attention all over the world. Dairy farming is a significant contributor to the emission of greenhouse gas emissions that cause climate change. This has prompted international dairy sectors to develop plans to reduce the greenhouse gas emission from dairy farming. The Chinese dairy sector is also exploring how to contribute to that reduction, while responding to the growing domestic demand for dairy products. In this study, we collected and analyzed technical data including greenhouse gas emissions of a pilot group of 15 farms where a greenhouse gas reduction method will be tested in the future. Next to that, we held a survey among farmers and stakeholders about the feasibility of mitigation options to reduce greenhouse gases. This was to explore how farmers will respond to recommended mitigation options. The results show that farmers with different herd sizes and different types of stakeholders have different opinions about the feasibility and attractiveness of mitigation options. The results are useful insights to further prepare the application of the tailored made approach to come to dairy farms that combine efficiency with low green house gas emisions.